Development of Mangrove Ecotourism Teaching Materials on Ecosystem Material to Improve Students' Science Literacy Skills: A Literature Review - Siti Diniah; Susilawati Susilawati; Gunawan Gunawan; Agil Al Idrus; Didik Santoso (Current Educational Review, 2025)
This study aims to identify and analyze the development of mangrove ecotourism teaching materials on ecosystem material to improve students' scientific literacy skills. Using the systematic literature review method, this study collected and analyzed scientific articles published between 2015 and 2024 through the Google Scholar and Sinta databases. The focus of the study includes keywords such as "Learning Materials Development", "Mangrove", "Ecosystem", and "Science Literacy". The results of the review show that environmental-based teaching materials, especially those that link the concept of mangrove ecotourism, can significantly improve students' scientific literacy. Learning approaches such as project-based learning and the use of interactive media have proven effective in attracting students' interest. This study confirms that the development of teaching materials that are contextual and relevant to students' environment can encourage a better understanding of ecosystems and the environmental issues they face. It is hoped that through direct experience and interaction with the mangrove ecosystem, students will not only gain theoretical knowledge, but will also be able to apply it in their daily lives, thereby contributing to environmental conservation. Thus, the development of mangrove ecotourism teaching materials is expected to be an effective tool in science education and increase students' environmental awareness